Learning needs as an intervention for Gen Y employees’ intention to stay and the mediating role of perceived organizational support - Othman, Zabedah; Mohamed, Rosmah; Kartar Singh, Jugindar Singh; Mohd Sujang, Farah Aqilah (Universal Publishers, 2020)
This paper aims to investigate the relationship between learning needs and generation Y employees' intention to stay. This study used a cross-sectional survey to collect primary data. The target population was generation Y employees working in the banking sector in Malaysia. Data was collected from 470 respondents, where a total of 230 respondents were males and 240 were females. Results from this study revealed that learning needs have a positive effect on the intention to stay by generation Y employees in the banking sector. In addition, perceived organizational support (POS) mediated the relationship between POS and intention to stay. The results confirmed that an increase in the learning needs of generation Y employees would increase their intention to stay. The study revealed that greater attention must be given to learning needs by organizational leaders and policymakers. This study contributes to the literature in human resource practices pertaining to learning needs as a critical intervention by organizations to increase the intention to stay by generation Y employees. The study is one of the first of its kind to address learning needs and the mediating role of perceived organizational support (POS) in the context of Gen Y's intention to stay in the banking sector in Malaysia.